APPLICATION OF MULTIVARIATE STATISTICAL METHODS IN DETERMINING SPATIAL DISTRIBUTION OF CHEMICAL ELEMENTS IN SOIL (POREČE REGION, NORTH MACEDONIA) (Geologica Macedonica, 2022)
The purpose of this study was to determine the presence of various chemical elements in soil samples in the region of Poreče, North Macedonia. For this purpose, 88 soil samples (44 topsoil, 0-5 cm, and 44 bottom soil samples, 20–30 cm) were collected and 57 elements were analyzed, from which 18 elements (Ag, Al, Ba, Ca, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, Sr, V and Zn) were analyzed by ICP-AES and additional 39 elements (B, Be, Bi, Cd, Ce, Co, Cs, Dy, Er, Eu, Ga, Gd, Ge, Hf, Hg, Ho, In, La, Lu, Mo, Nb, Nd, Pd, Pr, Pt, Rb, Sb, Sc, Sm, Sn, Ta, Tb, Ti, Tl, Tm, W, Y, Yb and Zr) were analyzed by ICP-MS. The obtained results were statistically processed to determine possible areas with pollution of soil with heavy metals. From the results of the analyzed elements by ICP-AES, 3 association lithogenic factors [F1 (Cu-Ni-Cr-V-Zn-Fe-Mn), F2 (Sr-Ca-Mg), F3 (Li-K-Al-Ba)] were determined. The distribution of the elements which are included in the lithogenic factors are incurred as a result of geological structures present in the investigated area (schists, carbonates, sandstones, and Neogene sediments).
Keywords: oil; potentially toxic elements; distribution; pollution; Poreče region; North Macedonia